Assistance to children in palliative care in the Brazilian scientific literature - Nathalia Rodrigues Garcia-Schinzari; Franklin Santana Santos (Sociedade de Pediatria de São Paulo, 2014)
Objective: To describe what has been published in Brazilian scientific literature regarding pediatric palliative care. Data sources: Bibliographic review with a descriptive approach. In LILACS and SciELO databases, the descriptors "palliative care", "child", "pediatrics", "terminal illness" and "death" were sought, from January 2002 to December 2011. The eight selected articles were analyzed according to year of publication, type of study, data collected, target population, pathology, professionals involved, types of care and main findings. Data synthesis: Regarding the year of publication, there was an increase in the number of publications related to pediatric palliative care. Regarding the type of study, four articles were literature reviews and four were qualitative researches. Data was collected mainly by semi-structured interviews. The participants of the majority of the studies were children's relatives and health professionals. The main pathology addressed was cancer and the nurses were the most frequently cited professionals. The types of care provided were related to physical aspects, general care and psychological, social and spiritual aspects (less emphasis). The main findings were: little emphasis on the children's needs, the importance of including the family in the care provided and the lack of preparation of the health team. Conclusions: Despite the difficulties and the challenges in establishing pediatric palliative care, many articles brought important considerations for the development of this practice in the country.